Tecnologías con potencial aplicación de remedición de lagos artificiales y naturales para la remoción de sales, sulfatos mejora de la oxigenación según principios de adaptación climática. (2023)
Lake Sochagota was built in 1955 for recreational use, built from a previous natural wetland. It is located on a high plateau (altitude 2496 m) in the department of Boyacá in the province of Paipa (Colombia), and occupies a total area of ​​1.8 km2. The deepest point of the Lake is 3.20 m. The lake is fed by a tributary of the Chicamocha river, the Honda-Río Salitre ravine